Distribution of brown seaweed producing alginate in Indonesia and the potential utilization - Subaryono Subaryono (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2011)
Brown seaweed producing alginate frequently obtained in Indonesian waters , especially fromgenus of Sargassum and Turbinaria. These seaweeds are wide distributed from Aceh to Papuawaters. There are 15 species of Sargassum and some species of Turbinaria in Indonesia. Thisseaweed were very potential used as a row material of alginate industry, with main market Chinaand Malaysia. Quality requirement for seaweed as row material for alginate industry in China werealginate content not less than 17%, viscosity 47 cP, and gel strength 139 g/cm2. Expansion ofalginate industry in Indonesia was limited by low continuity of row material production. Prospectiveutilization of this brown seaweed as a row material of drug/traditional herbal medicine were sohigh because its ability to reducing high blood glucose in diabetes patient and decelerate thegrowth of cancer cell. Natural seaweed collection were done at peak season production on dryseason, and help out to increase the welfare of seaweed collection farmer.